1995
DOI: 10.1093/bja/75.4.481
|View full text |Cite
|
Sign up to set email alerts
|

Use of the abbreviated mental test to detect postoperative delirium in elderly people

Abstract: We investigated the validity of the abbreviated mental test (AMT) as a guide to the diagnosis of delirium in 100 patients aged more than 65 yr. Patients were assessed using the AMT on the day before and on the third day after operation. Fifteen patients were delirious on the third postoperative day; 10 of 43 patients undergoing orthopaedic surgery and five of 57 patients undergoing non-orthopaedic surgery. Delirium developed in four of 16 patients with a preoperative AMT score less than 8 and in 11 of 84 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
9

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 5 publications
1
18
0
9
Order By: Relevance
“…The data from the sensitivity [47,48], it was initially designed to detect cognitive impairment [49]. The Aama 2011 trial had a lack of diagnostic criteria, replaced with Confusion Assessment Method (CAM) and Memorial Delirium Assessment Scale (MDAS) as the two rating scales for evaluating delirium [31].…”
Section: Discussionmentioning
confidence: 99%
“…The data from the sensitivity [47,48], it was initially designed to detect cognitive impairment [49]. The Aama 2011 trial had a lack of diagnostic criteria, replaced with Confusion Assessment Method (CAM) and Memorial Delirium Assessment Scale (MDAS) as the two rating scales for evaluating delirium [31].…”
Section: Discussionmentioning
confidence: 99%
“…Within our own survey, a small number of respondents reported using a variety of tools to diagnose delirium in their practice, citing tools which have not been validated for the use in acute stroke [26,43]. Some studies found a degree of usefulness in detecting cognitive changes using the AMT [44] and the MMSE [26] which might be due to delirium [51][52][53]; however, these tools are not specifically designed to detect delirium [27,49,54]. Some of our respondents reported difficulties in using diagnostic tools in stroke patients because of aphasia.…”
Section: Discussionmentioning
confidence: 99%
“…É frequentemente o quadro de apresentação de doenças físicas e toxicidade por fármacos. O diagnóstico precoce e o tratamento dos fatores desencadeantes podem minimizar a duração e a severidade desta desordem 51 .…”
Section: Aspectos Da Avaliação Cognitivaunclassified